2001
DOI: 10.1109/20.950908
|View full text |Cite
|
Sign up to set email alerts
|

Low noise FeAlSi soft magnetic under-layer for CoPtCrO double-layered perpendicular recording media

Abstract: FeAlSi multi-layered structure successfully reduced the noise compared with a mono-layered film. Optical surface analyzer also revealed that the films did not show any clear magnetic domains of spike noise source in the whole disk. TEM image of low noise film showed wide grain boundaries between 200 to 500 nm diameter FeAlSi grain clusters. The coercivities of films were significantly reduced when they were laminated. Along with the cluster isolation effect, the interlayer magnetic coupling of the multi-layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…2 shows an example of the time decay of the reproduced signal from CoPtCrO/[FeAlSi/C]n double-layer perpendicular media at room temperature [4]. A multilayered [FeAlSi/C]n underlayer structure was developed as a lownoise underlayer candidate [6], [7]. In the wide time range from 0.2 to 5 10 s, the signal decay rate was found better than 0.03 dB/decade even at low 10 kFCI (0.39 kfc/mm) recording density.…”
Section: Design Concept Of Double-layer Perpendicular Mediamentioning
confidence: 99%
“…2 shows an example of the time decay of the reproduced signal from CoPtCrO/[FeAlSi/C]n double-layer perpendicular media at room temperature [4]. A multilayered [FeAlSi/C]n underlayer structure was developed as a lownoise underlayer candidate [6], [7]. In the wide time range from 0.2 to 5 10 s, the signal decay rate was found better than 0.03 dB/decade even at low 10 kFCI (0.39 kfc/mm) recording density.…”
Section: Design Concept Of Double-layer Perpendicular Mediamentioning
confidence: 99%
“…114 The reduction of roughness was attributed to a reduction in the grain growth. Hikosaka et al have investigated FeAlSi/ C multilayers and have observed a reduction in atomic force microscopy ͑AFM͒ roughness and the noise.…”
Section: Noise Of Sulmentioning
confidence: 99%
“…Media noise, which is correlated with coercive force, must be reduced to enable soft magnetic multilayers to be used as backlayers. An FeAlSi soft magnetic multilayer with Ti intermediate layers has higher media noise and larger coercive force than an FeAlSi multilayer with C intermediate layers [1]. We previously reported that an as-deposited FeCSi soft magnetic multilayer with Cr or Ti intermediate layers, which has high media noise, has clear X-ray diffraction (XRD) peaks from the Fe phase although there are no XRD peaks in an as-deposited FeCSi multilayer with C intermediate layers, which has low media noise [4].…”
Section: Introductionmentioning
confidence: 98%
“…These multilayers effectively suppress the amplitude of spike noise [1][2][3][4]. Media noise, which is correlated with coercive force, must be reduced to enable soft magnetic multilayers to be used as backlayers.…”
Section: Introductionmentioning
confidence: 99%